Design of Control and Human Machine Interface (HMI) for Proton Exchange Membrane Fuel Cell - Kurniawan Kurniawan; Abdul Hamid Budiman; Ferri Hermawan; Anton Rahmawan (Purnomo Yusgiantoro Center, 2020)
Fuel cell is an electrochemical device that converts hydrogen and oxygen produces electrical energy continuously, water and heat as by product, which simultaneously. Proton Exchange Membrane Fuel Cell (PEMFC) operates with polymer electrolytes which are thin and proton permeable. Designing the control system, it is expected that the fuel cell operation could be in accordance with the predetermined process parameter design. In addition to the control system for fuel cell operations, a fuel cell protection or security system design is also carried out during operation in real condition. Referring to the block diagram or control system architecture and fuel cell operations that have been made, a detailed design will be made as a reference for the prototype of the control and protection system for operational and fuel cell testing and controlling. Making Standard operation procedure (SOP) is very helpful in the operation and avoids operating errors that can damage and harm caused.*The paper has been selected from a collaboration with IPST and 7th ICFCHT 2019 for a conference entitled